Perceptions of Quality of Work Life in Hospitality Jobs: The Role of Interpersonal and Supportive Relations at Work - Durão, Marília; Costa, Carlos; Carneiro, Maria João; Segovia-Pérez, Mónica (Journal of Tourism, Sustainability and Well-being, 2024)
This article addresses the concept of quality of work life (QWL) in the tourism and hospitality industry, emphasising its significance for employee well-being and retention. The focus is on the psychosocial working environment, particularly interpersonal and social interactions at the workplace, described in the existing literature as stressors and coping mechanisms crucial for managing high job demands. This is especially relevant considering the long working hours, heavy workloads, and high pressure that typify tourism and hospitality jobs. The study draws on 56 in-depth interviews with three groups of purposefully selected participants at various career stages in the hotel sector to examine the role of interpersonal and supportive relations in the workplace and its impact on the perceived QWL. Findings indicate that a positive working environment and strong social capital are pivotal in buffering job demands. Participants highly value workplace social relations, considering them essential aspects of their work life. Interpersonal and supportive relations at work emerge as the most influential dimension positively affecting QWL. These findings may have implications for organisational practices and policies that foster a supportive workplace culture, ultimately contributing to the well-being and retention of employees in the industry.